Modifikasi Biofoam Berbasis Pati Singkong dengan Serat Eceng Gondok dan Variasi Konsentrasi Plasticizer: Modification of Cassava Starch-Based Biofoam with Water Hyacinth Fiber and Concentration Variation of Plasticizer - Hutagalung, Sarawinda; Sibarani, James; Pramesti , Resia Yoan; Puspaningtya, Theresia Hellen Renata (KOVALEN: Jurnal Riset Kimia, 2024)
Biofoam is a plant-based alternative packaging. The biofoam was prepared by using the extrusion method and baking process. This research aims to determine the lowest ratio of PVA and glycerol in absorbing water and testing the mechanical properties of biofoam (tensile strength, biodegradation test and FTIR analysis. The best biofoam composition in absorbing water was obtained at a ratio of PVA: glycerol 8%. The results of biofoam characteristics obtained by the water absorption test were 9.76%, maximum bending strength was 9.20 MPa and biofoam can be degraded 100% on day 15. The results of FTIR analysis showed the presence of absorption spectra at wave numbers 3410,15 cm-1, which is a typical region of O-H functional groups (strong and broad) carbohydrates and polyphenols. Modification of starch with fiber and plasticizer in research improves the physicochemical characteristics of biofoam in terms of increasing water absorption and biofoam biodegradation. In contrast, in terms of mechanical properties, the bending strength of biofoam requires further research referring to the characteristics of biofoam mechanical properties toward SNI standards.